Embedded emergency department physical therapy versus usual care for acute low back pain: a protocol for the NEED-PT randomised trial. Issue 5 (24th May 2022) - Kim, Howard S; Muschong, Kayla M; Fishman, Ivy L; Schauer, Jacob M; Seitz, Amee L; Strickland, Kyle J; Lambert, Bruce L; McCarthy, Danielle M; Vu, My H; Ciolino, Jody D
Abstract : Introduction: Low back pain is a common problem and a substantial source of morbidity and disability worldwide. Patients frequently visit the emergency department (ED) for low back pain, but many experience persistent symptoms at 3 months despite frequent receipt of opioids. Although physical therapy interventions have been demonstrated to improve patient functioning in the outpatient setting, no randomised trial has yet to evaluate physical therapy in the ED setting. Methods and analysis: This is a single-centre cluster-randomised trial of an embedded ED physical therapy intervention for acute low back pain. We used a covariate-constrained approach to randomise individual physicians (clusters) at an urban academic ED in Chicago, Illinois, USA, to receive, or not receive, an embedded physical therapist on their primary treatment team to evaluate all patients with low back pain. We will then enrol individual ED patients with acute low back pain and allocate them to the embedded physical therapy or usual care study arms, depending on the randomisation assignment of their treating physician. We will follow patients to a primary endpoint of 3 months and compare a primary outcome of change in PROMIS-Pain Interference score and secondary outcomes of change in modified Oswestry Disability Index score and patient-reported opioid use. Our primary approach will be a modified intention-to-treat analysis, whereby all participants who complete at least one follow-up data time point will be included in analyses, regardless of their or their physicians' adherence to their assigned study arm. Ethics and dissemination: This trial is funded by the US Agency for Healthcare Research and Quality (R01HS027426) and was approved by the Northwestern University Institutional Review Board. All physician and patient participants will give written informed consent to study participation. Trial results will be submitted for presentation at scientific meetings and for publication in peer-reviewed journals. Trial registration number: ClinicalTrials.gov (NCT04921449 )